Peran Pendamping Sosial dalam Penanganan Konflik Keluarga Penerima Manfaat Program Keluarga Harapan - Aulia Sholichah Iman Nurchotimah; Bunyamin Maftuh; Elly Malihah; Yuni Harmawati (Faculty of Social Science, Universitas Negeri Malang, 2020)
Indonesia as a big country certainly is not free from various problems, one of which is poverty. Poverty in Indonesia has strong effect on the welfare of Indonesian citizens. “Program Keluarga Harapan” is a government program as an effort to reduce poverty in Indonesia. The purposes of this research were: (1) To determine the factors which caused conflict among the beneficiaries in Patikraja, Banyumas Regency, Central Javs; (2) To determine the role of social caseworker in managing conflicts on Program Keluarga Harapan beneficiaries in Patikraja, Banyumas regency. Methods used in this research was case study. Data collection techniques which were used in this study were observation, interview, and documentation. The results of this research were factors caused conflicts were the limited quota of the “Program Keluarga Harapan” and the social jealousy from the citizens who were not belong to the beneficiaries. Furthermore, the role of social caseworker in managing conflict on the Program Kelarga Harapan beneficiaries in Patikraja, Banyumas Regency, Central Java was by conductiong a mediation which used a strategy of communication and strongly hold on to the mediator principles.